Left main coronary artery atresia – Report of 2 cases - K.N. Srinivasan; I. Sathyamurthy; Neelagandan Manodaya (IHJ Cardiovascular Case Reports, 2022)
Left main coronary artery atresia (LMCAA) is a rare coronary anomaly. Usually they present with myocardial ischemia/infarction, heart failure, syncope due to ventricular arrhythmias or sudden death. Diagnosis is confirmed by CT or invasive coronary angiography. We are presenting two cases of LMCAA, who underwent off-pump coronary artery bypass surgery.